Manufacturers' Liability for Skincare Product Safety Violations in the Context of Law No. 8 of 1999: Pertanggungjawaban Produsen Skincare Atas Pelanggaran Keamanan Produk Dalam Perspektif Undang-Undang Nomor 8 Tahun 1999 - Ariqah, Nailah; Sudiro, Amad (Indonesian Journal of Law and Economics Review, 2026)
General Background: The rapid growth of Indonesia’s skincare industry has increased consumer dependence on cosmetic products, while the circulation of hazardous and non-compliant items continues to rise. Specific Background: Despite regulatory controls under Law Number 8 of 1999 on Consumer Protection, many producers still disregard safety standards, leading to health risks and information asymmetry. Knowledge Gap: Existing studies seldom integrate legal doctrine, regulatory mechanisms, and practical enforcement challenges in analyzing producers’ liability for unsafe skincare products. Aim: This study examines the scope of legal liability borne by skincare producers for product safety violations under the Consumer Protection Law. Results: Findings show that the law imposes strict obligations on producers to ensure product safety, provide accurate information, and comply with BPOM standards; violations may trigger civil compensation, administrative sanctions, or criminal penalties. Novelty: This research systematically synthesizes strict liability, product liability, and preventive legal duties within the context of Indonesia’s contemporary skincare market, highlighting gaps between normative mandates and real-market practices. Implications: Strengthening regulatory enforcement, transparency, and consumer awareness is crucial for achieving a fair, ethical, and accountable skincare industry. Highlights: Highlights producers’ strict liability for ensuring skincare product safety. Outlines civil, criminal, and administrative sanctions for safety violations. Emphasizes the gap between legal regulations and real-world industry practices. Keywords: Legal Liability, Skincare Producers, Product Safety, Consumer Protection, Strict Liability